Repetisi pada Lirik Lagu Dangdut Karya Denny Caknan (Repetition in the Lyrics of Dangdut Songs by Denny Caknan) - Muhammad Fatahillah; Sumarlam Sumarlam (Universitas Sebelas Maret, 2025)
This research aims to understand and describe the phenomenon of repetition in six popular songs by Denny Caknan. This study employed a descriptive qualitative method, using content analysis and a discourse analysis approach referring to Sumarlam (2024). The data were collected through listening and note-taking techniques from the lyrics of Denny Caknan's songs, specifically from his YouTube channel, DC Musik. The songs analyzed include